Wing Geometry Analysis of Aedes aegypti (Diptera, Culicidae), a Dengue Vi-rus Vector, from Multiple Geographical Locations of Samut Songkhram, Thailand - Tanawat Chaiphongpachara; Nattapon Juijayen; Kitthisak Khlaeo Chansukh (Tehran University of Medical Sciences, 2018)
Background: Dengue Haemorrhagic Fever (DHF) is a mosquito-borne disease and remains a major public health problem, especially in tropical and temperate countries. Studying wing morphometric of Aedes aegypti as a mosquito vector of DHF can help to better understand biological process of the mosquito adaptation to the environment. We aimed to study the geometric morphometric of Ae. aegypti from multiple geographical areas. Methods: Samples were collected from Samut Songkhram Province in Thailand, including coastal, residential and cultivated areas, by Ovitrap once per month during Oct to Nov 2016. Results: According to size variation analysis of Ae. aegypti, the female mosquito in a cultivated area was significantly different from those in the coastal and residential areas (P< 0.05). Whereas male Ae. aegypti in a cultivated area were significantly different from those in a residential area (P< 0.05). The shape variation of both female and male Ae. aegypti from all areas was statistically different (P< 0.05). Conclusion: Normally, living organisms, including mosquitoes, are adapted to their environment. The studied geographical locations affect Ae. aegypti morphology.